THE PREVALENCE, PRACTICE AND ATTITUDE TOWARD NEONATAL JAUNDICE AMONG SAUDI MOTHERS (CAHIERS MAGELLANES-NS, 2024)
Background: Neonatal jaundice NNJ is a common problem that threatens a substantial number of newborns, and its occurrence is as high as 55.2% among full-term neonates. Although in most of the time, symptoms are usually mild and resolve on their own, it is considered a highly dangerous neonatal condition, therefore calling for early identification. The specific objectives of this study were: To evaluate the understanding, perception and behavior of mothers in Saudi Arabia on neonatal jaundice, alsoto identify the incidence of NNJ and risk indicators in Saudi Arabia. Methods: A self-administered survey was carried out from July to November, 2024 by using convenience sampling to recruit 686 Saudi mothers aged 18 years and above with at least one child. Quantitative data were analyzed using Microsoft Excel and statistical analysis was done using SPSS software program. Results: Participants’ average age was 38.1 years, a majority being married at 90.2% and 67.2% having a bachelor’s degree. Unfavorably, 85.3% of the mothers had poor understanding about NNJ despite 89.5% of them perceiving it as a yellowish discoloration of the skin and the eyes. A total of 30% of mothers reported that jaundice developing in the first 36 hours is abnormal and only half of the participants knew its potential triggers; 64% of them stated that breastfeeding can cause jaundice. Despite the fact that 92% of them are willing to seek hospital treatment, only 7.1% has demonstrated a high level of knowledge and thus decision-making deficiency. Sex, number of children, level of education and prior experiences showed signification correlations with the level of knowledge regarding NNJ. Conclusion: The conclusions drawn from the author’s work show poor awareness of neonatal jaundice among potential mothers and high readiness to receive medical aid. This is why educational campaigns designed to increase knowledge about NNJ are needed more than ever in Saudi Arabia. Subsequently, there is increased possibility of improving the status of maternal and neonatal health, underlining the necessity of clearly organized public health campaigns aimed at raising awareness of the female population in the matters of neonatal morbidity.